Optimal tax structure for consumption and income inequality : an empirical assessment - Afonso, António (2018)
In the present empirical analysis, we try to assess the impact of taxation on investment growth. In particular, and by using gross _xed capital formation as a proxy for investment, we intend to evaluate the impact of the taxation structure in investment dynamics, in a short and a long-run perspectives. This empirical exercise was conducted for all OECD countries, during the 1980-2015 period. Through panel data econometric techniques, we find optimal tax-investment threshold values, especially higher for short-term than for long-term horizon. In addition, we find optimal income taxation around 9%, in percentage of GDP, an average optimal value of 12.7% for consumption taxes to promote annual investment growth.